Blind tiger - Brown, Sandra, 1948- (New York : Grand Central Publishing, 2021)
"Thatcher Hutton, a war-weary soldier, is on the way back to his cowboy life. On the day he arrives in Foley, Texas, a local woman goes missing. Thatcher, the only stranger in town, is suspected of her abduction and worse. Standing between him and exoneration are a corrupt mayor, a crooked sheriff, a notorious cathouse madam, a sly bootlegger, feuding moonshiners, and a young widow whose soft features conceal an iron will. Laurel Plummer is destitute, but determined to dictate her own future. She plunges into the lucrative regional industry, much to the dislike of the good ol' boys who have ruled supreme, and her success quickly makes her a target for cutthroat competitors. Laurel and Thatcher find themselves on opposite sides of a moonshine war, where blood flows as freely as whiskey."--
Keywords: Soldiers -- Fiction; Cowboys -- Fiction; Missing persons -- Fiction; Abduction -- Fiction; Prohibition -- Texas -- Fiction; Moonshine (Liquor) -- Fiction; Texas -- History -- 1846-1950 -- Fiction; Large type books; Thrillers (Fiction); Historical fiction